It Suddenly Occurred: Extensive Subcutaneous Emphysema after Bipolar Transurethral Resection of Prostate - Murat Bagcioglu; Mert Ali Karadag; Ramazan Kocaaslan; Cafer Mutlu Sarikas; Mustafa Gok; Omer Erkam Arslan (Case Reports in Urology)
Subcutaneous emphysema is a very rare and good-natured complication after transurethral resection of prostate (TURP). It has been reported as colon perforation, diverticulitis, and bladder perforation associated complication previously. We report the first case of a wide subcutaneous emphysema due to microperforations of prostatic capsule, without a bladder perforation after TURP. Any sign of clinic situation should lead to ceasing of the procedure immediately; otherwise, it can cause a life-threatening problem of abdominal compartment syndrome.